Optimization of Vehicle Routing Problem with Tight Time Windows, Short travel time and Re-used Vehicles (VRPTSR) for Aircraft Refueling in Airport Using Ant Colony Optimization Algorithm - Nurlita Gamayanti; Mochammad Sahal; Adi Wibisono (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Scheduling in aircraft refueling has an important role in aviation. Scheduling of aircraft refueling is called Airport Ground Service Scheduling (AGSS) that can be formulated as Vehicle Routing Problem with Tight time windows, Short travel time and Re-used Vehicles (VRPTSR) This research is focusing in scheduling design for aircraft refueling with refueller truck in Juanda Airport, Surabaya, so minimum amount of truck will be used using Ant Colony optimization. The result shows that Ant Colony optimization could do scheduling in refueling well so minimum amount of truck will be used. Keywords: Scheduling, Vehicle Routing Problem with Tight time windows, Short travel time and Re-used Vehicles,  Ant Colony Optimization